Mesenchymal Stromal Cell Therapy in Ischemia/Reperfusion Injury. (15th July 2015) - Rowart, Pascal; Erpicum, Pauline; Detry, Olivier; Weekers, Laurent; Grégoire, Céline; Lechanteur, Chantal; Briquet, Alexandra; Beguin, Yves; Krzesinski, Jean-Marie; Jouret, François
Abstract : Ischemia/reperfusion injury (IRI) represents a worldwide public health issue of increasing incidence. IRI may virtually affect all organs and tissues and is associated with significant morbidity and mortality. Particularly, the duration of blood supply deprivation has been recognized as a critical factor in stroke, hemorrhagic shock, or myocardial infarction, as well as in solid organ transplantation (SOT). Pathophysiologically, IRI causes multiple cellular and tissular metabolic and architectural changes. Furthermore, the reperfusion of ischemic tissues induces both local and systemic inflammation. In the particular field of SOT, IRI is an unavoidable event, which conditions both short- and long-term outcomes of graft function and survival. Clinically, the treatment of patients with IRI mostly relies on supportive maneuvers since no specific target-oriented therapy has been validated thus far. In the present review, we summarize the current literature on mesenchymal stromal cells (MSC) and their potential use as cell therapy in IRI. MSC have demonstrated immunomodulatory, anti-inflammatory, and tissue repair properties in rodent studies and in preliminary clinical trials, which may open novel avenues in the management of IRI and SOT.